Conecta-SUS: the use of social networks in the dissemination of information on actions and services of the Unified Health (Research, Society and Development, 2021)
The objective of this study is to discuss the impact of the Conecta-SUS project as a health education strategy on the Unified Health System, through the profiles of social networks using information and communication technology: Instagram®, Facebook® and Twitter®. The Organic Health Law enacted in 1990, regulates health actions and services throughout the national territory and establishes principles, guidelines and objectives of the Unified Health System, mentioning that the citizen has the right to know about the functioning of this system, through the dissemination of information about the potential of health services and their use by the user. Conecta-SUS is an extension project of the Medicine Course at the Federal University of Juiz de Fora, Governador Valadares, with the interdisciplinary participation of students and professors of health courses. Accounts were created on these social networks, managed by the coordinating professor and a student of the project. The publications were divided into three content standards: theoretical, practical and referring to Covid-19. 136 publications were made: 30 theoretical, 44 practical, 62 referring to Covid-19. The publications received 5230 likes, 4694 on Instagram®, 355 on Facebook®, 181 on Twitter®. Therefore, the digital construction of knowledge has a relevant impact, both for teachers, students and the general population, as it allows them to have quick and secure access, in simple language, to various information, often unknown or even not understood about the Health Unic System.